Combination chemotherapy of drug-resistant Trypanosoma brucei rhodesiense infections in mice using DL-alpha-difluoromethylornithine and standard trypanocides. - Bacchi, C J (1994)
Combinations of DL-alpha-difluoromethylornithine (DFMO; eflornithine; Ornidyl) with either suramin or melarsen oxide were found to be effective against acute laboratory model infections with Trypanosoma brucei rhodesiense. We used clinical isolates known to be resistant to these drugs when used singly. An infection with a melarsen oxide-refractory isolate was cured by a combination of low-dose DFMO (0.5% in the drinking water) plus low-dose suramin (1 mg/kg of body weight given intraperitoneally). Another strain, moderately resistant to arsenical drugs, was cured with combinations of 4% DFMO with 5 mg of melarsen oxide per kg. Furthermore, a combination of DFMO (2% in the drinking water) and suramin (20 mg/kg) provided a 100% cure rate in a central nervous system model, although the same doses of these drugs used singly were completely ineffective. The synergism of DFMO and suramin against an acute infection was improved when suramin was given at the end of the DFMO administration. No adverse interactions were observed when high doses of DFMO combined with high doses of suramin were administered to uninfected mice. These results suggest that combinations of DFMO and suramin should be examined clinically for activity in arsenical-drug-refractory cases of East African sleeping sickness.